Aspirations and progression of event management graduates: A study of career development - Barron, P.; Ali-Knight, Jane (Council for the Australian University Tourism and Hospitality Education Inc, 2017)
The provision of event management education in the higher education sector has grown significantly in recent years, yet little is known of the circumstances of the increasing number of graduates from these programmes. This paper examines the motivations, the expectations and the career aspirations of festival and event management graduates from a post-92 university in Scotland. Adopting a mixed methods approach, a quantitative on line survey was used to contact festival and event management alumni who had graduated during the period 2007 to 2012. This was followed by in depth interviews with 15 students. This study found that graduates felt academically prepared for working life in the industry, but lacked the practical skills required. In general, graduates held a positive view and could foresee long-term careers in the festival and event industry.